Modeling and Analysis of Fouling Behaviour in Plate and Frame Heat Exchanger - Stephen K. Ogbonnaya, Oluseyi O. Ajayi, Ohiozua D. Ohijeagbon & Mercy Ogbonnaya (Covenant Journal of Engineering Technology, 2018)
The fouling of heat exchangers in the oil and gas industry is not only a recurring challenge in refineries but it is also becoming a challenge in crude oil production and treatment facilities where heat exchangers are deployed to cool the crude oil temperature downstream of stabilization system prior to storage. A predictive mitigation approach to addressing fouling in heat exchangers remains the most viable option to avoid production train capacity limitations, unplanned shutdown and attendant loss of revenue. Considerable researches have been carried out which lead to the development of models used for predicting fouling resistances in shell and tube heat exchangers. However, this study focused on evaluation of the performance of a plate and frame heat exchanger utilized in cooling of crude oil prior to storage in a cargo tank for export. It also developed a fouling resistance suitable for forecasting the exchanger performance and predicting the maintenance management scheme. The data employed were continuously measured for three years and employed for the analysis.Â  It found that the lower the hot stream approach temperature, the more the fouling resistance. In addition, the work validates that as the fouling resistance increases with time, the efficiency of the plate and frame heat exchanger diminishes.